Estudo de parâmetros pré-laminares e laminares da cabeça do nervo óptico em olhos com e sem glaucoma, utilizando o módulo Enhanced Depth Imaging da tomografia de coerência óptica - Lopes, Flavio Siqueira Santos [UNIFESP] (2020)
Objective: To study the morphological parameters of the optic nerve head (ONH) in patients with and without glaucoma using the enhanced depth imaging examination optical coherence tomography (EDI OCT), evaluating its reproducibility, relationships between structure and function and diagnostic capacity of laminar and pre laminar parameters. Methods: An observational cross-sectional study was conducted, where patients with open-angle glaucoma were prospectively recruited. All participants were submitted to a complete ophthalmological exam, automated perimetry (Swedish Interactive Threshold Algorithm - Standard 24–2; Carl Zeiss Meditec, Dublin, CA) and EDI OCT (Spectralis; Heidelberg Engineering Co., Heidelberg, Germany). The following parameters of the ONH were evaluated: area and thickness of the lamina cribrosa (LC), area and prelaminar neural tissue (PLNT) thickness, bruch membrane opening (BMO), average, superior and inferior measurements of the minimum distance between BMO and the internal limiting membrane (aBMO-MRW, sBMO-MRW and iBMO-MRW, respectively) and anterior depth of LC (ALD). In addition, the peripapillary retinal nerve fiber layer (pRNFL) thickness was also evaluated. Results: Of the 81 participants initially evaluated, 73 were included in the final analysis (39 in the glaucoma group and 34 in the control group). The mean age of patients in the control group was 60.7 ± 10.7 years old and in the glaucoma group 64.9 ± 11.9 years old (p < 0.122), mean deviation (MD) was -1 ±0.9 dB in the control group and -9.4 ± 7.4 dB in the glaucoma group (p < 0.01). All parameters evaluated differed significantly between glaucomatous and healthy eyes (p≤0.045). Eyes with glaucoma presented a significantly lower mean LC and PLNT thickness (p≤0.01) when compared to controls. Significant correlations were found between structure and function of visual function index (VFI) and PLNT area (R2=0.20, p=0.017), aBMO-MRW (R2=0.35, p≤0.001), sBMO-MRW (R2=0.21, p=0.012) and iBMO-MRW (R2=0.27, p=0.002). No significant correlation was found for LC area or ALD (p≥0.452). The comparison of the values of the areas under the characteristic curve of receiver operation (AUC) between the different parameters of the OCT EDI did not reveal significant differences between aBMO-MRW (0.995; CI95%: 0.942 to 1.000), PNLT area (0.968; CI95%: 0.898 to 0.995) and average pRNFL thickness (0.975; 95% CI: 0.906 to 0.997; p≥0.089). The sensitivity values at 80% specificity were: PLNT area = 92.3%, aBMO-MRW = 97.4% and average pRNFL thickness = 94.9%. Conclusion: Comparing the diagnostic ability and the relation between structure and function of the different ONH parameters derived from EDI OCT, we found better results for neural tissue-based indices compared to laminar parameters. The new parameter evaluated, PLNT area, presented diagnostic ability similar to the pRNFL thickness and aBMO-MRW. Since the evaluation of prelaminar parameters (aBMO-MRW and PNLT area) showed the ability to identify glaucomatous eyes similar to the conventional analysis of pRNFL thickness, we believe the best way to make the combined use of these parameters should be further investigated and also the best patient profile for each individual analysis.